2013
DOI: 10.1155/2013/507832
|View full text |Cite
|
Sign up to set email alerts
|

The Protection of Salidroside of the Heart against Acute Exhaustive Injury and Molecular Mechanism in Rat

Abstract: Objective. To investigate the protection of salidroside of the heart against acute exhaustive injury and its mechanism of antioxidative stress and MAPKs signal transduction. Method. Adult male SD rats were divided into four groups randomly. Cardiomyocytes ultrastructure was observed by optical microscopy and transmission electron microscopy. The contents of CK, CK-MB, LDH, MDA, and SOD were determined by ELISA method, and the phosphorylation degrees of ERK and p38 MAPK were assayed by Western blotting. Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…These results indicated that RCE promotes cardiomyocyte survival under acute hypobaric hypoxia exposure by p38MAPK, but not ERK, signaling pathway in heart tissue. These results are similar to those observed in the acute exhaustive rodent model where salidroside regulates MAPK signaling pathways, through modification of ROS generation [15]. Thus, the regulatory effect of RCE on MAPK pathways might again be due to the antioxidant property of RCE.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These results indicated that RCE promotes cardiomyocyte survival under acute hypobaric hypoxia exposure by p38MAPK, but not ERK, signaling pathway in heart tissue. These results are similar to those observed in the acute exhaustive rodent model where salidroside regulates MAPK signaling pathways, through modification of ROS generation [15]. Thus, the regulatory effect of RCE on MAPK pathways might again be due to the antioxidant property of RCE.…”
Section: Discussionsupporting
confidence: 86%
“…In a rodent model of exhaustive exercise, salidroside, a major bioactive compound of RCE, exerted a cardioprotective effect via its antioxidant activity [15]. In this study, we have shown that RCE reduces biomarkers of cardiac oxidative stress (ROS, MDA, and protein carbonyl) in rat myocardium.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…한편으로 급격하고 과도한 운동은 심근세포의 산소 소모 를 증가시키므로 활성산소종(reactive oxygen species, ROS) 생성을 증가시키고 심장의 구조적, 기능적 및 대사적 장애를 초래한다 16,17) . Fig.…”
Section: Sab의 보호효능에 대해 실험동물을 사용한 In Vivo 연구들unclassified